2020
DOI: 10.3390/v12080858
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circovirus Genome in a Chinstrap Penguin (Pygoscelis antarcticus) and Adélie Penguin (Pygoscelis adeliae) on the Antarctic Peninsula

Abstract: Circoviruses infect a variety of animal species and have small (~1.8–2.2 kb) circular single-stranded DNA genomes. Recently a penguin circovirus (PenCV) was identified associated with an Adélie Penguin (Pygoscelis adeliae) with feather disorder and in the cloacal swabs of three asymptomatic Adélie Penguins at Cape Crozier, Antarctica. A total of 75 cloacal swab samples obtained from adults and chicks of three species of penguin (genus: Pygoscelis) from seven Antarctic breeding colonies (South Shetland Islands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
10
1
1
Order By: Relevance
“…AntCM8 genotype II was unique in this study as being the only genotype found in two distinct host species: An adult Gentoo Penguin and two adult Chinstrap Penguins nesting at the same colony on Booth Island, with >99.9% shared genome-wide identity. One of these adult Chinstrap Penguins was recently found also to carry a penguin circovirus [46]. Three species (each as a single genotype) of Antarctic circular molecules that encode Reps (AntCM10-12) were identified in this sample set, all from a single Chinstrap colony in the South Shetland Islands, where two genotypes, those which only contain a rep gene (rep: 963-1335 nts), were found in multiple individuals.…”
Section: Distribution Of Viruses and Viral-like Molecules Across Sampling Sites And Penguin Speciesmentioning
confidence: 94%
See 2 more Smart Citations
“…AntCM8 genotype II was unique in this study as being the only genotype found in two distinct host species: An adult Gentoo Penguin and two adult Chinstrap Penguins nesting at the same colony on Booth Island, with >99.9% shared genome-wide identity. One of these adult Chinstrap Penguins was recently found also to carry a penguin circovirus [46]. Three species (each as a single genotype) of Antarctic circular molecules that encode Reps (AntCM10-12) were identified in this sample set, all from a single Chinstrap colony in the South Shetland Islands, where two genotypes, those which only contain a rep gene (rep: 963-1335 nts), were found in multiple individuals.…”
Section: Distribution Of Viruses and Viral-like Molecules Across Sampling Sites And Penguin Speciesmentioning
confidence: 94%
“…The phylum Cressdnaviricota includes seven viral families (Bacilladnaviridae, Circoviridae, Geminiviridae, Genomoviridae, Nanoviridae, Redondoviridae and Smacoviridae), the Reps of the satellite nucleic acids in the family Alphasatellitidae, and a suite of viral groups that have been loosely labeled CRESS DNA viruses. Within these named viral families in the order Cressdnaviricota, only two Penguin circovirus genomes (family Circoviridae) had previously been recovered from this same sample set, found in a Chinstrap Penguin and an Adélie Penguin [46]. CRESS DNA viruses that cannot be classified into the eight families above have been identified primarily through viral metagenomic approaches from a variety of samples, including animal tissues, as highlighted in the recent report by Tisza et al [47], fecal samples [48][49][50] and environmental samples including plant leaves [51], soil [52], wastewater [53][54][55], seawater [56], freshwater [57], and sea spray [58].…”
Section: Identification Of Viruses and Viral-like Molecules From Cloacal Swabsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are common viruses belonging to 16 HA (H1-H16) and 9 NA (N1-N9) serotypes [4,5]. Occasionally, avian influenza viruses can cross the species barrier and acquire the ability to infect other animals, including swine [6], equines [7], seals [8], dogs [9], wild and domestic cats [10], civets [11], nonhuman primates [12], chinstrap penguins [13], martens, and humans [14][15][16]. Some biological factors, such as the host cell receptor (sialic acid) and its linkages, play critical roles in cross-species transmission [17].…”
Section: Introductionmentioning
confidence: 99%
“…Circoviruses, which are small, circular, single-stranded DNA-bearing viruses, have been identified in penguins, and a penguin circovirus (PenCV) has been described in the past. In their article, Levy et al [ 20 ] visited seven Antarctic breeding colonies in different regions of Antarctica and collected 75 cloacal swab samples from adults and chicks of three species of penguins. Samples were screened for PenCV DNA, and two new genetic variants were identified: one in an Adélie Penguin ( Pygoscelis adeliae ) and another in a Chinstrap Penguin ( Pygoscelis antarcticus ).…”
mentioning
confidence: 99%